Analysis of the differential transcriptome expression profiles during prenatal muscle tissue development in Diqing Tibetan pigs - Luo, Shuyuan; Bai, Ying; Li, Xinpeng; Jin, Siqi; Yan, Dawei; Dong, Xinxing (Frontiers in Veterinary Science, 2025)
Since the number of muscle fibers in pigs is largely fixed after birth, the formation of muscle fibers during the embryonic stage plays a crucial role in determining postnatal growth performance and meat production potential. In this study, we used large Diqing Tibetan pigs (LTP) and small Diqing Tibetan pigs (STP), which show significant differences in postnatal growth rate and meat yield, as research models. We employed RNA-seq for transcriptome sequencing and applied differential expression analysis combined with weighted gene co-expression network analysis (WGCNA) to compare their gene expression profiles and identify potential regulatory differences during key stages of embryonic muscle development. Longissimus dorsi muscle samples were collected from both groups at three critical developmental stages—embryonic day 55 (E55), embryonic day 75 (E75), and at birth (D0)—for transcriptome sequencing. Differential expression analysis revealed that the higher meat yield observed in LTP compared with STP may be attributed to a stronger capacity for secondary muscle fiber formation during the embryonic stage. Furthermore, WGCNA identified candidate genes that may specifically regulate muscle development in LTP across the three key developmental stages. These findings provide valuable insights into the molecular regulatory networks underlying muscle development and growth potential in Diqing Tibetan pigs.